Mapping global coral vulnerability to stony coral tissue loss disease: implications for biosecurity and conservation - Lafferty, Kevin D.; Strona, Giovanni (Frontiers in Marine Science, 2025)
Stony Coral Tissue Loss Disease (SCTLD) has devastated Caribbean coral reefs since 2014, but its potential for global impact remains uncertain. We developed predictive models to assess the worldwide vulnerability of coral reefs to SCTLD under different origin and spread hypotheses. Using random forest regression models incorporating coral taxonomy and zooxanthellae clade associations from 52 taxa, we projected SCTLD susceptibility and mortality patterns globally using six indices: Mean susceptibility per genus per location, Summed susceptibilities across genera per location, Summed susceptibilities across genera per realm, Mean mortality per genus per location, Summed mortalities across genera per location, and Summed mortalities across genera per realm. Models demonstrated strong predictive performance (R² = 0.57 for susceptibility; R² = 0.73 for mortality) and revealed that about 7% of coral genera per location are potentially susceptible to SCTLD. While mean susceptibility and mortality per genus were highest in the Tropical Atlantic, the summed susceptibility and mortality across genera were much higher in the biodiverse Central Indo-Pacific. Natural barriers could limit SCTLD’s spread, including the mid-Atlantic gap and the low diversity of the Tropical Eastern Pacific, supporting the contained disease hypothesis. However, the widespread distribution of susceptible genera across coral reef realms indicates significant vulnerability should SCTLD circumvent these barriers through human-mediated transport, particularly via ballast water or the aquarium trade. If SCTLD is an invasive pathogen originating in the Pacific, as shipping patterns for the aquarium trade suggest, mortality in its native range would likely be lower than our projections. These findings point to targeted intervention strategies, including enhanced monitoring at key locations, assessment of biosecurity needs in high-risk areas, and prioritized conservation efforts in vulnerable high-diversity regions to prevent SCTLD from spreading globally.